Antireflection film and image display device
The antireflection film with a high tin oxide content primer layer addresses the delamination issue in acidic environments, providing enhanced adhesion and durability for applications like automotive displays.
Patent Information
- Application Number
- JP2023113507
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-11
AI Technical Summary
Existing antireflection films with a primer layer made of indium tin oxide (ITO) are prone to interlayer delamination when exposed to acids, limiting their application in environments requiring acid resistance, such as automotive applications.
An antireflection film design with a primer layer containing indium tin oxide as a main component, where the amount of tin oxide is 15% by weight or more, ensuring enhanced adhesion between the hard coat layer and the antireflection layer, and optionally including an antifouling layer for improved durability.
The film exhibits excellent acid resistance and weather resistance, maintaining adhesion under acidic conditions and UV exposure, suitable for applications requiring durability.
Smart Images

Figure 2025011409000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-reflection film and an image display device. [Background technology]
[0002] An anti-reflection film is disposed on the viewing side of an image display device such as a liquid crystal display or an organic EL display for the purposes of preventing deterioration in image quality due to reflection of external light, improving contrast, etc. The anti-reflection film has an anti-reflection layer made of a laminate of multiple thin films with different refractive indices on a transparent film substrate.
[0003] For example, Patent Document 1 discloses an antireflection film in which a primer layer containing indium tin oxide (ITO) is provided on a hard coat layer, and an antireflection layer made of a plurality of thin films is formed thereon. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-266665 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors have found through their research that when an anti-reflective film provided with a general ITO film as a primer layer is brought into contact with an acid such as sulfuric acid, delamination (e.g., delamination between the anti-reflective layer and the hard coat layer) is likely to occur. For this reason, it may be difficult to apply an anti-reflective film provided with a general ITO film as a primer layer to applications requiring acid resistance (resistance to corrosion by acid). Examples of applications requiring acid resistance include automotive applications (on-board applications) in which sulfuric acid is used in the battery fluid.
[0006] In view of the above, an object of the present invention is to provide an antireflection film having excellent acid resistance, and an image display device using the antireflection film. [Means for solving the problem]
[0007] <Aspects of the present invention> The present invention includes the following aspects.
[0008] [1] An antireflection film having a transparent film substrate, a hard coat layer, a primer layer, and an antireflection layer in this order, the antireflection layer is a laminate of a plurality of thin films having different refractive indices, The primer layer is a thin film containing indium tin oxide as a main component, and the amount of tin oxide relative to the total amount of indium oxide and tin oxide is 15% by weight or more.
[0009] [2] The anti-reflection film according to [1], wherein the primer layer contains tin oxide in an amount of 60% by weight or less based on the total amount of indium oxide and tin oxide.
[0010] [3] The anti-reflection film according to [1] or [2] above, wherein the thickness of the primer layer is 0.5 nm or more and 20 nm or less.
[0011] [4] The antireflection film according to any one of [1] to [3] above, further comprising an antifouling layer disposed on the antireflection layer opposite to the primer layer side.
[0012] [5] The antireflection film according to any one of [1] to [4] above, wherein the hard coat layer contains particles with a number average primary particle diameter of less than 1.0 μm.
[0013] [6] The antireflection film according to any one of [1] to [5] above, further comprising a pressure-sensitive adhesive layer disposed on the opposite side of the transparent film substrate from the hard coat layer.
[0014] [7] An image display device comprising: an image display panel; and the anti-reflection film according to any one of [1] to [6] above, disposed on a viewing side of the image display panel. Effect of the Invention
[0015] According to the present invention, it is possible to provide an antireflection film having excellent acid resistance, and an image display device using the antireflection film. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view showing an example of an anti-reflection film according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of the antireflection film according to the present invention. [Diagram 3] 1 is a cross-sectional view showing an example of an image display device according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Preferred embodiments of the present invention will be described in detail below, but the present invention is not limited thereto. In addition, all academic and patent documents described in this specification are incorporated herein by reference.
[0018] First, the terms used in this specification are explained. The "refractive index" is the refractive index for light with a wavelength of 550 nm in an atmosphere at a temperature of 23°C. The "principal surface" of a layered material (more specifically, a transparent film substrate, a hard coat layer, a primer layer, an anti-reflection layer, an antifouling layer, an adhesive layer, etc.) refers to a surface perpendicular to the thickness direction of the layered material. Unless otherwise specified, the numerical value of the thickness (film thickness) of each layer constituting the anti-reflection film is the arithmetic average value of 10 measured values obtained by randomly selecting 10 measurement points from an image of a cross section cut in the thickness direction of the layer and measuring the thickness of the selected 10 measurement points.
[0019] The "major component" of a thin film (layer) means the component that is contained in the thin film in the largest amount by weight, unless otherwise specified. The "solid content" refers to the non-volatile components in the composition, e.g., components other than the solvent.
[0020] Unless otherwise specified, the number-average primary particle diameter of particles is the number-average value of the circle-equivalent diameters (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) of 100 primary particles measured using a scanning electron microscope and image processing software (e.g., "ImageJ" manufactured by the National Institutes of Health, USA).
[0021] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. In addition, when the polymer name is represented by adding "based" after the compound name, it means that the repeating unit of the polymer is derived from the compound or its derivative, unless otherwise specified. The components and functional groups exemplified in this specification may be used alone or in combination of two or more types, unless otherwise specified.
[0022] The drawings referred to in the following description are intended to illustrate each component in a schematic manner for ease of understanding, and the size, number, shape, etc. of each component shown in the drawings may differ from the actual size, number, shape, etc., for convenience of drawing. Also, for convenience of explanation, in the drawings described later, the same components as those in the drawings described earlier may be given the same reference numerals, and explanations thereof may be omitted.
[0023] <First embodiment: Anti-reflection film> The anti-reflection film according to the first embodiment of the present invention is an anti-reflection film (laminate) having a transparent film substrate, a hard coat layer, a primer layer, and an anti-reflection layer in this order. The anti-reflection layer is a laminate of multiple thin films with different refractive indices. The primer layer is a thin film containing indium tin oxide as a main component, and the amount of tin oxide relative to the total of indium oxide and tin oxide is 15% by weight or more.
[0024] Hereinafter, the amount of tin oxide (unit: weight %) relative to the total of indium oxide and tin oxide in the primer layer (100 weight %) may be simply referred to as "the amount of tin oxide in the primer layer" or "the amount of tin oxide."
[0025] The antireflection film according to the first embodiment has the above-mentioned configuration and is therefore excellent in acid resistance, the reason for which is presumed to be as follows.
[0026] In the anti-reflection film according to the first embodiment, a thin film containing indium tin oxide as a main component is provided as a primer layer for improving the adhesion between the hard coat layer and the anti-reflection layer. In addition, the amount of tin oxide in the primer layer of the anti-reflection film according to the first embodiment is 15% by weight or more. Therefore, in the anti-reflection film according to the first embodiment, the primer layer tends to be less susceptible to corrosion by acid. Therefore, the anti-reflection film according to the first embodiment has excellent acid resistance because the adhesion between the hard coat layer and the anti-reflection layer is ensured even when it comes into contact with acid.
[0027] In addition, since the anti-reflection film according to the first embodiment has the above-mentioned configuration, it is possible to ensure adhesion between layers when irradiated with ultraviolet rays. Hereinafter, the property of ensuring adhesion between layers when irradiated with ultraviolet rays may be referred to as "weather resistance".
[0028] In the first embodiment, in order to obtain an anti-reflection film having superior acid resistance, the amount of tin oxide in the primer layer is preferably 18% by weight or more, more preferably 20% by weight or more, even more preferably 22% by weight or more, even more preferably 24% by weight or more, and may be 25% by weight or more, 30% by weight or more, 35% by weight or more, or 40% by weight or more.
[0029] In the first embodiment, in order to obtain an anti-reflection film having excellent transparency, the amount of tin oxide in the primer layer is preferably 60% by weight or less, more preferably 55% by weight or less, even more preferably 50% by weight or less, and may be 45% by weight or less.
[0030] The configuration of the antireflection film according to the first embodiment will be described below with reference to the drawings. FIG. 1 is a cross-sectional view showing an example of the antireflection film according to the first embodiment. The antireflection film 10 shown in FIG. 1 has a transparent film substrate 11, a hard coat layer 12, a primer layer 13, and an antireflection layer 14 in this order. The primer layer 13 is in contact with both the hard coat layer 12 and the antireflection layer 14. The primer layer 13 is a thin film containing indium tin oxide as a main component, and the amount of tin oxide relative to the total of indium oxide and tin oxide is 15% by weight or more.
[0031] The antireflection film 10 further includes an antifouling layer 19 disposed on the side of the antireflection layer 14 opposite to the primer layer 13. That is, the antireflection film 10 includes a transparent film substrate 11, a hard coat layer 12, a primer layer 13, an antireflection layer 14, and an antifouling layer 19 in this order.
[0032] The antireflection layer 14 has four layers, namely, a high refractive index layer 15, a low refractive index layer 16, a high refractive index layer 17, and a low refractive index layer 18, in this order from the primer layer 13 side. Details of the high refractive index layer and the low refractive index layer will be described later. The antireflection layer of the antireflection film is not limited to a four-layer structure like the antireflection layer 14, and may be a two-layer structure, a three-layer structure, a five-layer structure, or a laminate structure of six or more layers. The antireflection layer of the antireflection film is preferably an alternating laminate of two or more high refractive index layers and two or more low refractive index layers. In order to reduce reflection at the air interface, it is preferable that the outermost layer (the layer farthest from the hard coat layer 12) of the antireflection layer of the antireflection film is a low refractive index layer.
[0033] The antireflection film according to the first embodiment may have a layer structure different from that of the antireflection film 10 shown in Fig. 1. For example, the antireflection film according to the first embodiment may be an antireflection film 20 further including a pressure-sensitive adhesive layer 21 arranged on the side of the transparent film substrate 11 opposite to the hard coat layer 12 side, as shown in Fig. 2.
[0034] The adhesive constituting the adhesive layer 21 is not particularly limited, and can be appropriately selected and used from transparent adhesives having a base polymer such as an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyvinyl ether, a vinyl acetate-vinyl chloride copolymer, a modified polyolefin, an epoxy resin, a fluorine resin, a natural rubber, a synthetic rubber, etc. The thickness of the adhesive layer 21 is not particularly limited, but is preferably 5 μm or more and 100 μm or less from the viewpoint of achieving both a thin layer property and adhesiveness.
[0035] A release liner (not shown) may be temporarily attached to the main surface of the adhesive layer 21 opposite to the transparent film substrate 11 side. The release liner protects the surface of the adhesive layer 21, for example, until the anti-reflection film 20 is bonded to an image display panel 101 (see FIG. 3) described later. A plastic film made of acrylic, polyolefin, cyclic polyolefin, polyester, or the like is preferably used as a constituent material of the release liner. The thickness of the release liner is, for example, 5 μm or more and 200 μm or less. The surface of the release liner is preferably subjected to a release treatment. Examples of materials of the release agent used in the release treatment include silicone-based materials, fluorine-based materials, long-chain alkyl-based materials, and fatty acid amide-based materials.
[0036] Although the configuration of the antireflection film according to the first embodiment has been described above with reference to the drawings, the antireflection film according to the present invention is not limited to the above-mentioned configuration.
[0037] For example, the antireflection film according to the present invention may be an antireflection film that does not have an antifouling layer. Also, the antireflection film according to the present invention may have an optical functional layer different from the layers included in the above-mentioned configuration (transparent film substrate, hard coat layer, primer layer, antireflection layer, and antifouling layer).
[0038] Next, the elements of the anti-reflection film according to the first embodiment will be described.
[0039] [Transparent film substrate] The transparent film substrate is, for example, a transparent resin film having flexibility. Examples of materials constituting the transparent film substrate include polyester resin, polyolefin resin, polystyrene resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyamide resin, polyimide resin, cellulose resin, norbornene resin, polyarylate resin, and polyvinyl alcohol resin. Examples of polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of cellulose resin include triacetyl cellulose (TAC). These materials may be used alone or in combination of two or more. From the viewpoint of transparency and strength, the material of the transparent film substrate is preferably one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, more preferably one selected from the group consisting of PET, COP, and TAC, and even more preferably TAC. In other words, as the transparent film substrate, a type of film selected from the group consisting of polyester resin film, polyolefin resin film, and cellulose resin film is preferable, a type of film selected from the group consisting of PET film, COP film, and TAC film is more preferable, and a TAC film is even more preferable.
[0040] From the viewpoint of strength, the transparent film substrate has a thickness of preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. From the viewpoint of handleability, the transparent film substrate has a thickness of preferably 300 μm or less, and more preferably 200 μm or less.
[0041] One or both main surfaces of the transparent film substrate may be subjected to a surface modification treatment, such as a corona treatment, a plasma treatment, an ozone treatment, a primer treatment, a glow treatment, or a coupling agent treatment.
[0042] From the viewpoint of improving the transparency of the antireflection film, the total light transmittance (JIS K 7375-2008) of the transparent film substrate is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more and 100% or less.
[0043] [Hard coat layer] The hard coat layer is a layer that enhances mechanical properties such as hardness and elastic modulus of the anti-reflection film. The hard coat layer is, for example, made of a cured product of a curable resin composition (composition for forming a hard coat layer). Examples of the curable resin contained in the curable resin composition include polyester resin, acrylic resin, urethane resin, urethane acrylate resin, amide resin, silicone resin, epoxy resin, and melamine resin. These curable resins may be used alone or in combination of two or more kinds. From the viewpoint of enhancing the hardness of the hard coat layer, the curable resin is preferably one or more kinds selected from the group consisting of acrylic resin and urethane acrylate resin, and more preferably urethane acrylate resin.
[0044] In addition, examples of the curable resin composition include an ultraviolet-curable resin composition and a thermosetting resin composition. From the viewpoint of improving the productivity of the anti-reflection film, the curable resin composition is preferably an ultraviolet-curable resin composition. The ultraviolet-curable resin composition includes one or more selected from the group consisting of an ultraviolet-curable monomer, an ultraviolet-curable oligomer, and an ultraviolet-curable polymer. A specific example of the ultraviolet-curable resin composition includes a hard coat layer forming composition described in JP 2016-179686 A.
[0045] The curable resin composition may also contain fine particles. By blending fine particles in the curable resin composition, it is possible to adjust the hardness, surface roughness, refractive index, and antiglare properties of the hard coat layer. Examples of the fine particles include metal (or semi-metal) oxide particles, glass particles, and organic particles. Examples of materials for metal (or semi-metal) oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of materials for organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.
[0046] The curable resin composition may contain particles having a number average primary particle diameter of less than 1.0 μm (hereinafter, may be referred to as "nanoparticles") as the fine particles. That is, the hard coat layer may contain nanoparticles. When the hard coat layer is made of a cured product of a curable resin composition containing nanoparticles, fine irregularities are formed on the surface of the hard coat layer, and the adhesion between the hard coat layer and a layer (e.g., a primer layer) formed thereon tends to be improved.
[0047] From the viewpoint of forming a fine uneven shape that contributes to improving adhesion, the number average primary particle diameter of the nanoparticles is preferably 20 nm or more and 80 nm or less, more preferably 25 nm or more and 70 nm or less, and even more preferably 30 nm or more and 60 nm or less.
[0048] As the material of the nanoparticles, inorganic oxides are preferred. Examples of inorganic oxides include oxides of metals (or semi-metals) such as silicon oxide (silica), titanium oxide, aluminum oxide, zirconium oxide, niobium oxide, zinc oxide, tin oxide, cerium oxide, and magnesium oxide. The inorganic oxide may be a composite oxide of a plurality of (semi-)metals. Among the inorganic oxides exemplified above, silicon oxide is preferred because of its high effect of improving adhesion. In other words, as the nanoparticles, silicon oxide particles (silica particles) are preferred. Functional groups such as acrylic groups and epoxy groups may be introduced to the surfaces of inorganic oxide particles as nanoparticles in order to improve adhesion and affinity with resins.
[0049] The amount of nanoparticles in the hard coat layer is preferably 5 parts by weight or more, and may be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, based on 100 parts by weight of the curable resin. If the amount of nanoparticles is 5 parts by weight or more, the adhesion with the layer formed on the hard coat layer can be further improved. The upper limit of the amount of nanoparticles in the hard coat layer is, for example, 90 parts by weight, preferably 80 parts by weight, and may be 70 parts by weight, based on 100 parts by weight of the curable resin.
[0050] The thickness of the hard coat layer is preferably 1 μm or more, more preferably 2 μm or more, from the viewpoint of increasing the hardness of the hard coat layer, and is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 35 μm or less, and even more preferably 30 μm or less, from the viewpoint of ensuring the flexibility of the antireflection film.
[0051] The main surface of the hard coat layer opposite to the transparent film substrate may be surface-modified. Examples of surface-modifying treatments include plasma treatment, corona treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment. In order to increase the adhesion between the hard coat layer and a layer (e.g., a primer layer described later) provided on the side opposite to the transparent film substrate of the hard coat layer, it is preferable that the main surface of the hard coat layer opposite to the transparent film substrate is plasma-treated.
[0052] [Primer layer] The primer layer is a layer for enhancing adhesion between the hard coat layer and the anti-reflection layer. In this embodiment, the primer layer is a thin film mainly composed of indium tin oxide (ITO). By including ITO as a main component in the primer layer, it is possible to obtain a primer layer having excellent transparency while enhancing adhesion between the hard coat layer and the anti-reflection layer. In addition, by including ITO as a main component in the primer layer, it is possible to provide the anti-reflection film with appropriate antistatic properties.
[0053] The primer layer may contain oxides other than indium oxide and tin oxide, but in order to further improve the adhesion between the hard coat layer and the anti-reflection layer, the content of ITO in the primer layer is preferably 90% by weight or more, more preferably 99% by weight or more, based on the total amount of the primer layer. Hereinafter, a thin film mainly composed of ITO may be referred to as an "ITO layer."
[0054] In order to ensure the transparency of the primer layer while improving the adhesion between the hard coat layer and the antireflection layer, the thickness of the primer layer is preferably 0.5 nm or more and 20 nm or less, more preferably 0.5 nm or more and 10 nm or less, and even more preferably 1.0 nm or more and 10 nm or less.
[0055] [Anti-reflection layer] An anti-reflection layer is made up of two or more thin layers with different refractive indices. In general, the optical film thickness (product of refractive index and thickness) of the thin films of an anti-reflection layer is adjusted so that the reversed phases of incident light and reflected light cancel each other out. By making the anti-reflection layer a multi-layer laminate of two or more thin films with different refractive indices, it is possible to reduce the reflectance over a wide wavelength range of visible light.
[0056] Examples of materials for the thin film constituting the antireflection layer include metal (or semimetal) oxides, nitrides, fluorides, etc. The antireflection layer is preferably an alternating laminate of high refractive index layers and low refractive index layers.
[0057] The high refractive index layer has a refractive index of, for example, 1.9 or more, and preferably 2.0 or more. Examples of materials for the high refractive index layer include titanium oxide and niobium oxide (Nb 2 O 5 Examples of the material for the low refractive index layer include silicon oxide (SiO ), zirconium oxide, tantalum oxide, zinc oxide, indium oxide, and antimony-doped tin oxide (ATO). Among these, at least one selected from the group consisting of titanium oxide and niobium oxide is preferable. The refractive index of the low refractive index layer is, for example, 1.6 or less, and preferably 1.5 or less. Examples of the material for the low refractive index layer include silicon oxide (SiO ), 2 Examples of the thin film include titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, and lanthanum fluoride. Among these, silicon oxide is preferable. In particular, it is preferable to alternately laminate a niobium oxide thin film as a high refractive index layer and a silicon oxide thin film as a low refractive index layer. In addition to the low refractive index layer and the high refractive index layer, a medium refractive index layer having a refractive index of more than 1.6 and less than 1.9 may be provided.
[0058] The thickness of the high refractive index layer and the low refractive index layer is preferably 5 nm or more and 200 nm or less, and more preferably 10 nm or more and 150 nm or less. The thickness of each layer may be designed so that the reflectance of visible light is small according to the refractive index and the lamination structure. For example, the lamination structure of the high refractive index layer and the low refractive index layer may be a four-layer structure consisting of a high refractive index layer with an optical thickness of 20 nm or more and 55 nm or less, a low refractive index layer with an optical thickness of 25 nm or more and 55 nm or less, a high refractive index layer with an optical thickness of 80 nm or more and 270 nm or less, and a low refractive index layer with an optical thickness of 100 nm or more and 150 nm or less, from the hard coat layer side.
[0059] When the antireflection layer is a four-layer alternating laminate in which niobium oxide thin films as high refractive index layers and silicon oxide thin films as low refractive index layers are alternately laminated, the antireflection layer may be configured to have, from the hard coat layer side, a niobium oxide thin film with a thickness of 5 nm to 20 nm, a silicon oxide thin film with a thickness of 10 nm to 40 nm, a niobium oxide thin film with a thickness of 65 nm to 120 nm, and a silicon oxide thin film with a thickness of 60 nm to 100 nm, in that order.
[0060] In order to obtain an antireflection film having excellent bending resistance, the thickness of the antireflection layer is preferably 140 nm or more and 280 nm or less, more preferably 170 nm or more and 280 nm or less, even more preferably 180 nm or more and 260 nm or less, and even more preferably 190 nm or more and 250 nm or less. In this specification, the "thickness of the antireflection layer" refers to the sum of the thicknesses of the layers constituting the antireflection layer (total thickness).
[0061] [Anti-stain layer] The anti-reflection film preferably has an anti-soiling layer on the side opposite to the primer layer of the anti-reflection layer, and more preferably has an anti-soiling layer as the outermost layer of the anti-reflection film. By providing the anti-soiling layer, for example, the influence of contamination from the external environment (fingerprints, hand dirt, dust, etc.) can be reduced, and contaminants attached to the surface of the anti-reflection film can be easily removed.
[0062] In order to prevent the antireflection performance of the antireflection layer from being deteriorated, it is preferable that the antifouling layer has a small refractive index difference from the outermost layer (e.g., a low refractive index layer) of the antireflection layer. The refractive index of the antifouling layer is preferably 1.6 or less, more preferably 1.55 or less.
[0063] As a material for the antifouling layer, a fluorine-containing compound is preferred. A fluorine-containing compound can contribute to lowering the refractive index while having excellent antifouling properties. Among them, an alkoxysilane compound containing a perfluoropolyether skeleton is preferred because it has excellent water repellency and can exhibit high antifouling properties. An example of an alkoxysilane compound containing a perfluoropolyether skeleton is an alkoxysilane compound having a plurality of linear or branched perfluoroalkylene oxide units having 1 to 4 carbon atoms. An example of a linear or branched perfluoroalkylene oxide unit having 1 to 4 carbon atoms is a perfluoromethylene oxide unit (-CF 2 O-), perfluoroethylene oxide unit (-CF 2 CF 2O-), perfluoropropylene oxide unit (-CF 2 CF 2 CF 2 O-), perfluoroisopropylene oxide unit (-CF(CF 3 )CF 2 O-) and the like.
[0064] The thickness of the antifouling layer is, for example, 2 nm or more and 20 nm or less. The thicker the antifouling layer, the more the antifouling property tends to improve. The thickness of the antifouling layer is preferably 5 nm or more, and more preferably 6 nm or more. On the other hand, from the viewpoint of improving the antiglare property, the thickness of the antifouling layer is preferably 15 nm or less.
[0065] [Preferred embodiment of anti-reflection film] In order to obtain an antireflection film having excellent acid resistance while ensuring weather resistance and transparency, the antireflection film according to the first embodiment preferably satisfies the following condition 1, more preferably satisfies the following condition 2, and even more preferably satisfies the following condition 3. Condition 1: The amount of tin oxide in the primer layer is 15% by weight or more and 60% by weight or less. Condition 2: The above condition 1 is satisfied, and the thickness of the primer layer is 0.5 nm or more and 20 nm or less. Condition 3: The above condition 2 is satisfied, and the hard coat layer contains particles with a number average primary particle diameter of less than 1.0 μm.
[0066] [Anti-reflection film manufacturing method] Next, there will be described a preferred method for producing the antireflection film according to the first embodiment. Hereinafter, the preferred method for producing the antireflection film according to the first embodiment may be referred to as production method M.
[0067] The manufacturing method M includes, for example, a primer layer forming step and an antireflection layer forming step. The manufacturing method M may include steps (other steps) other than the primer layer forming step and the antireflection layer forming step. Examples of the other steps include a hard coat layer forming step, a surface treatment step of the hard coat layer, and an antifouling layer forming step, which will be described later.
[0068] Hereinafter, each step of the example of the manufacturing method M will be described.
[0069] (Hard coat layer forming process) The hard coat layer forming step is a step of forming a hard coat layer on one main surface of a transparent film substrate. For example, a curable resin composition (composition for forming a hard coat layer) is applied to one main surface of a transparent film substrate, and the hard coat layer is formed by removing the solvent and curing the resin as necessary. The composition for forming a hard coat layer contains, for example, the above-mentioned curable resin and a polymerization initiator (e.g., a photopolymerization initiator), and contains a solvent capable of dissolving or dispersing these components as necessary.
[0070] In addition to the above components, the composition for forming a hard coat layer may contain additives such as nanoparticles, particles having a number-average primary particle diameter of 1.0 μm or more, leveling agents, viscosity modifiers (thixotropic agents, thickeners, etc.), antistatic agents, antiblocking agents, dispersants, dispersion stabilizers, antioxidants, UV absorbers, antifoaming agents, surfactants, and lubricants.
[0071] The coating method of the hard coat layer forming composition may be any suitable method such as bar coating, roll coating, gravure coating, rod coating, slot orifice coating, curtain coating, fountain coating, comma coating, etc. The drying temperature of the coating film after coating may be set to an appropriate temperature depending on the composition of the hard coat layer forming composition, for example, 50°C or higher and 150°C or lower. When the resin component in the hard coat layer forming composition is a thermosetting resin, the coating film is cured by heating. When the resin component in the hard coat layer forming composition is a photocurable resin, the coating film is cured by irradiating it with active energy rays such as ultraviolet rays. The integrated light amount of the irradiated light is preferably 100 mJ / cm. 2 More than 500mJ / cm 2 The following is the result.
[0072] (Surface treatment process of hard coat layer) In the surface treatment process of the hard coat layer, the main surface of the hard coat layer opposite to the transparent film substrate side is surface modified. Examples of the surface modification treatment include plasma treatment, corona treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment. When the surface modification treatment is plasma treatment, for example, argon gas is used as the inert gas. The discharge power in the plasma treatment is, for example, 50 W or more and 300 W or less. The pressure condition in the plasma treatment is, for example, 0.1 Pa or more and 2.5 Pa or less.
[0073] (Primer layer formation process) The primer layer forming step is a step of forming (forming) a primer layer on the hard coat layer. The method of forming the primer layer is not particularly limited, and may be either a wet coating method or a dry coating method. Dry coating methods such as vacuum deposition, CVD, and sputtering are preferred because they can form a thin film with a uniform thickness. From the viewpoint of increasing productivity, the method of forming the primer layer is preferably a method of forming a film using a roll-to-roll sputtering film forming device (roll-to-roll sputtering method).
[0074] In the roll-to-roll sputtering method, for example, a primer layer and an anti-reflection layer can be continuously formed while transporting a long film (for example, a transparent film substrate on which a hard coat layer is formed) in the longitudinal direction (MD direction). In the sputtering method, the film is formed while introducing an inert gas such as argon, and if necessary, a reactive gas such as oxygen, into the film formation chamber. When forming an ITO layer as the primer layer, the ITO layer can be formed by sputtering using either an oxide target or reactive sputtering using a metal (or semi-metal) target.
[0075] Examples of power sources for carrying out the sputtering method include DC power sources, AC power sources, RF power sources, and MFAC power sources (AC power sources with a frequency band of several kHz to several MHz). The discharge power in the sputtering method is, for example, 1 kW to 100 kW, and preferably 1 kW to 50 kW. The surface temperature of the film-forming roll when carrying out the sputtering method is, for example, -25°C to 25°C, and preferably -20°C to 0°C. The pressure in the film-forming chamber when carrying out the sputtering method is preferably 0.01 Pa to 10 Pa, more preferably 0.05 Pa to 5 Pa, and even more preferably 0.1 Pa to 1 Pa.
[0076] (Anti-reflection layer formation process) The anti-reflection layer forming step is a step of forming an anti-reflection layer on the primer layer. The method of forming the anti-reflection layer is not particularly limited, and may be either a wet coating method or a dry coating method. Dry coating methods such as vacuum deposition, CVD, and sputtering are preferred because they can form a thin film with a uniform thickness. From the viewpoint of increasing productivity, the method of forming the primer layer is preferably a method of forming a film using a roll-to-roll sputtering film forming device (roll-to-roll sputtering method). When performing the sputtering method in the anti-reflection layer forming step, the film forming conditions can be appropriately set, for example, among the conditions described above (primer layer forming step).
[0077] (Anti-stain layer formation process) The antifouling layer forming step is a step of forming an antifouling layer on the side opposite to the primer layer side of the antireflection layer. In the antifouling layer forming step, for example, a fluorine-containing compound is used as a material to form the antifouling layer by a dry coating method. Examples of the dry coating method include a vacuum deposition method, a sputtering method, and a CVD method, and the vacuum deposition method is preferred.
[0078] <Second embodiment: Image display device> Next, an image display device according to a second embodiment of the present invention will be described. The image display device according to the second embodiment includes an image display panel and an anti-reflection film according to the first embodiment arranged on the viewing side of the image display panel. Hereinafter, the description of the contents overlapping with the first embodiment will be omitted.
[0079] Fig. 3 is a cross-sectional view showing an example of an image display device according to the second embodiment. The image display device 100 shown in Fig. 3 includes an image display panel 101 and an antireflection film 10, which is an example of the antireflection film according to the first embodiment, arranged on the viewing side (upper side in Fig. 3) of the image display panel 101. In the image display device 100, a transparent film substrate 11 of the antireflection film 10 and the image display panel 101 are bonded together via an adhesive layer 21.
[0080] The image display panel 101 can be exemplified by an image display panel including an image display cell such as a liquid crystal cell or an organic EL cell.
[0081] The image display device according to the second embodiment has an anti-reflection film disposed on the viewing side of the image display panel, which reduces reflection of external light and provides excellent visibility. In addition, the image display device according to the second embodiment has excellent acid resistance because it includes the anti-reflection film according to the first embodiment. EXAMPLES
[0082] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0083] <Preparation of Antireflection Film of Example 1> [Hard coat layer formation process] The ultraviolet-curable resin composition of the urethane acrylate type containing silica particles having a number-average primary particle diameter of 50 nm ("Beamset 577" manufactured by Arakawa Chemical Industries Co., Ltd.), 0.1 parts by weight of silicone resin particles ("Tospearl 130" manufactured by Momentive Performance Materials Japan, Inc., average particle diameter: 3.0 μm, refractive index: 1.43, true specific gravity: 1.32), 4.0 parts by weight of cross-linked polymethyl methacrylate (PMMA) particles ("Techpolymer SSX-103" manufactured by Sekisui Chemical Co., Ltd., average particle diameter: 3.0 μm, refractive index: 1.50, true specific gravity: 1.20), 2.0 parts by weight of a thixotropic agent ("Sumecton SAN" manufactured by Kunimine Kogyo Co., Ltd., a synthetic smectite which is an organic clay), and a photopolymerization initiator (IGM 3.0 parts by weight of a silicone leveling agent ("Omnirad127" manufactured by Resins Co., Ltd.) and 0.15 parts by weight of a silicone-based leveling agent ("Polyflow LE303" manufactured by Kyoeisha Chemical Co., Ltd.) were mixed and diluted with butyl acetate to obtain a composition HC1 for forming a hard coat layer with a solid content concentration of 40% by weight. Next, the composition HC1 for forming a hard coat layer obtained by the above procedure was applied to one main surface of a TAC film ("Fujitac TG60UL" manufactured by Fujifilm Co., Ltd., thickness: 60 μm) as a transparent film substrate to form a coating film. Next, this coating film was dried by heating at a temperature of 60° C. for 60 seconds, and then cured by ultraviolet irradiation. When irradiating with ultraviolet rays, a high-pressure mercury lamp was used as a light source, ultraviolet rays with a wavelength of 365 nm were used, and the accumulated light amount was 300 mJ / cm 2 2 As a result, a hard coat layer with a thickness of 6 μm was formed on the TAC film.
[0084] [Surface treatment process for hard coat layer] Next, the surface of the hard coat layer was plasma-treated by a roll-to-roll type plasma treatment device while conveying the TAC film on which the hard coat layer was formed under a vacuum atmosphere of 1.0 Pa. During the plasma treatment, argon gas was used as an inert gas, and the discharge power was set to 100 W. As a result, a laminate (hereinafter, sometimes referred to as "optical film F1") including the TAC film and the plasma-treated hard coat layer was obtained.
[0085] [Primer layer formation process] Next, the optical film F1 was introduced into a roll-to-roll sputtering deposition apparatus, and the deposition chamber was filled with 1×10 -4 The pressure was reduced to 100 Pa. Next, while conveying the optical film F1, argon gas and oxygen gas were introduced in a volume ratio of 100:13, the surface temperature of the film-forming roll was set to -8°C, and an ITO layer (primer layer) having a thickness of 1.5 nm was formed on the hard coat layer by a sputtering method. For the formation of the primer layer, an ITO target containing indium oxide and tin oxide in a weight ratio of 85:15 was used as the target material. In addition, when forming the film by the sputtering method, the power source was an MFAC power source, the discharge power was 4.5 kW, and the pressure in the film-forming chamber was 0.2 Pa.
[0086] [Anti-reflection layer formation process] Following the formation of the primer layer, a roll-to-roll sputtering deposition device was used to transport the optical film F1 after the primer layer was formed, while a first layer: 12 nm thick Nb 2 O 5 layer (refractive index: 2.33), second layer: SiO 27 nm thick 2 layer (refractive index: 1.46), third layer: 108 nm thick Nb 2 O 5 layer, and the fourth layer: SiO 2 with a thickness of 86 nm 2The layers were deposited in this order. As a result, an anti-reflection layer having a four-layer structure (a four-layer structure consisting of a first layer, a second layer, a third layer, and a fourth layer) was formed on the primer layer. In the deposition of each of the first to fourth layers, the surface temperature of the deposition roll was set to -8°C, the power source was an MFAC power source, and the pressure in the deposition chamber was set to 0.7 Pa. In addition, in the deposition of the first layer, a Nb target was used, argon gas and oxygen gas were introduced in a volume ratio of 100:5, and the discharge power was set to 13.0 kW. In the deposition of the second layer, a Si target was used, argon gas and oxygen gas were introduced in a volume ratio of 100:33, and the discharge power was set to 25.5 kW. In the deposition of the third layer, a Nb target was used, argon gas and oxygen gas were introduced in a volume ratio of 100:13, and the discharge power was set to 27.5 kW. In forming the fourth layer, a Si target was used, argon gas and oxygen gas were introduced at a volume ratio of 100:30, and the discharge power was set to 20.5 kW.
[0087] [Anti-stain layer formation process] A coating agent ("SHIN-ETSU SUBELYN KY1903-1" manufactured by Shin-Etsu Chemical Co., Ltd., active ingredient: alkoxysilane compound containing a perfluoropolyether skeleton) was dried and solidified and used as a deposition source, and an antifouling layer having a thickness of 8 nm was formed on the antireflection layer by vacuum deposition at a heating temperature of the deposition source of 260° C. This resulted in an antireflection film (antireflection film of Example 1) having a TAC film, a hard coat layer, a primer layer, an antireflection layer, and an antifouling layer in this order.
[0088] <Preparation of anti-reflection film of Example 2> An anti-reflection film of Example 2 was obtained by the same production method as in Example 1, except that in the primer layer formation step, an ITO target containing indium oxide and tin oxide in a weight ratio of 80:20 was used as the target material.
[0089] <Preparation of anti-reflection film of Example 3> An anti-reflection film of Example 3 was obtained by the same production method as in Example 1, except that in the primer layer formation step, an ITO target containing indium oxide and tin oxide in a weight ratio of 75:25 was used as the target material.
[0090] <Preparation of anti-reflection film of Example 4> An anti-reflection film of Example 4 was obtained by the same production method as in Example 1, except that in the primer layer formation step, an ITO target containing indium oxide and tin oxide in a weight ratio of 70:30 was used as the target material.
[0091] <Preparation of anti-reflection film of Example 5> An anti-reflection film of Example 5 was obtained by the same production method as in Example 1, except that in the primer layer formation step, an ITO target containing indium oxide and tin oxide in a weight ratio of 60:40 was used as the target material.
[0092] <Preparation of anti-reflection film of Comparative Example 1> An anti-reflection film of Comparative Example 1 was obtained by the same production method as in Example 1, except that in the primer layer formation step, an ITO target containing indium oxide and tin oxide in a weight ratio of 90:10 was used as the target material.
[0093] <Preparation of Antireflection Film of Reference Example 1> An antireflection film of Reference Example 1 was obtained by the same production method as in Example 1, except that the primer layer formation step was changed to the following procedure.
[0094] [Primer layer formation step of Reference Example 1] The optical film F1 was introduced into a roll-to-roll sputtering deposition device, and the deposition chamber was filled with 1×10 -4The pressure was reduced to 100 Pa. Next, while conveying the optical film F1, argon gas and oxygen gas were introduced at a volume ratio of 100:9, the surface temperature of the film-forming roll was set to -8°C, and a SiOx layer (x<2) having a thickness of 3.0 nm was formed on the hard coat layer by sputtering. A Si target was used as a target material for forming the primer layer (SiOx layer). In addition, when forming the film by the sputtering method, the power source was an MFAC power source, the discharge power was 4.5 kW, and the pressure in the film-forming chamber was 0.7 Pa.
[0095] <Preparation of Antireflection Film of Reference Example 2> An antireflection film of Reference Example 2 was obtained by the same production method as in Example 1, except that the primer layer formation step was changed to the following procedure.
[0096] [Primer layer formation step of Reference Example 2] The optical film F1 was introduced into a roll-to-roll sputtering deposition device, and the deposition chamber was filled with 1×10 -4 The pressure was reduced to 100 Pa. Next, while transporting the optical film F1, argon gas and oxygen gas were introduced at a volume ratio of 100:10, the surface temperature of the film-forming roll was set to -8°C, and a TiOx layer (x<2) having a thickness of 1.5 nm was formed on the hard coat layer by sputtering. A Ti target was used as a target material for forming the primer layer (TiOx layer). In addition, when forming the film by the sputtering method, the power source was an MFAC power source, the discharge power was 4.5 kW, and the pressure in the film-forming chamber was 0.7 Pa.
[0097] <Measurement and evaluation methods> [Method of measuring the amount of tin oxide] The amount of tin oxide in the primer layer of the anti-reflection film to be measured (specifically, any of the anti-reflection films of Examples 1 to 5 and Comparative Example 1) was measured by the following procedure. First, a primer layer having a thickness of 1.5 nm was formed on the hard coat layer of the optical film F1 under the same conditions as those for forming the primer layer of the anti-reflection film to be measured. Next, the elemental composition of the obtained primer layer was measured using a scanning X-ray fluorescence analyzer ("ZSX PrimusII" manufactured by Rigaku Corporation). Then, the amount of tin oxide relative to the total amount of indium oxide and tin oxide (unit: weight %) was calculated.
[0098] [Acid resistance evaluation method] A drop of sulfuric acid aqueous solution (37% (1+3)-sulfuric acid, manufactured by Kishida Chemical Co., Ltd., sulfuric acid concentration: 37% by weight, water concentration: 63% by weight) was dropped with a dropper onto the antifouling layer surface of the antireflection film to be evaluated (specifically, any of the antireflection films of Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2) and allowed to stand for 22 hours in an atmosphere of 23°C temperature and 50% relative humidity. Next, the antifouling layer surface was washed with water, and the presence or absence of delamination in the antireflection film was visually confirmed. When there was no delamination, it was evaluated as A (excellent acid resistance). On the other hand, when there was delamination, it was evaluated as B (not excellent acid resistance).
[0099] [Weather resistance evaluation method] First, a 5 mm thick glass plate was attached to the main surface of the TAC film side of the antireflection film to be evaluated (specifically, any of the antireflection films of Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2) via an adhesive to obtain an evaluation sample. Next, the evaluation sample was placed in a weather resistance evaluation device (Iwasaki Electric Co., Ltd.'s "Eyesuper SUV-W161") and irradiated with ultraviolet light from the antifouling layer side under the following conditions.
[0100] (Ultraviolet irradiation conditions) Black Panel Temperature (BPT): 85℃ Relative humidity: 45% UV intensity: 150mW / cm 2 Irradiation time: 32.5 hours
[0101] Next, 100 squares were formed on the antifouling layer side of the anti-reflection film after UV irradiation, and a cross-cut peel test was performed according to JIS K5400 (cross-cut test method). The number of peeled squares was counted, and the weather resistance was evaluated according to the following criteria. "Peeling" means that peeling occurred over 1 / 4 or more of the area of one square. A: The number of peeled squares was 9 or less. B: The number of peeled squares was 10 or more.
[0102] When the result was A, it was evaluated as having "excellent weather resistance." On the other hand, when the result was B, it was evaluated as having "not excellent weather resistance."
[0103] <Result> Table 1 shows the type of oxide constituting the primer layer, the amount of tin oxide, the evaluation results of acid resistance, and the evaluation results of weather resistance for Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2. In Table 1, "-" means that no measurement was performed.
[0104] [Table 1]
[0105] As shown in Table 1, the amount of tin oxide in the primer layer was 15% by weight or more in Examples 1 to 5. In Examples 1 to 5, the evaluation results of acid resistance were A. Thus, the antireflection films of Examples 1 to 5 were excellent in acid resistance.
[0106] As shown in Table 1, the amount of tin oxide in the primer layer was less than 15% by weight in Comparative Example 1. In Comparative Example 1, the evaluation result of acid resistance was B. Therefore, the antireflection film of Comparative Example 1 did not have excellent acid resistance.
[0107] Regarding weather resistance, all the samples were rated A (excellent weather resistance) except for Reference Example 2 in which a TiOx layer was provided as a primer layer.
[0108] The above results demonstrate that the present invention can provide an antireflection film having excellent acid resistance. [Explanation of symbols]
[0109] 10, 20 Anti-reflective film 11 Transparent film substrate 12 Hard coat layer 13 Primer layer 14 Anti-reflection layer 19 Antifouling layer 21 Adhesive layer 100 Image display device 101 Image display panel
Claims
1. An antireflection film having a transparent film substrate, a hard coat layer, a primer layer, and an antireflection layer in this order, the antireflection layer is a laminate of a plurality of thin films having different refractive indices, The primer layer is a thin film containing indium tin oxide as a main component, and the amount of tin oxide relative to the total amount of indium oxide and tin oxide is 15% by weight or more.
2. 2. The anti-reflection film according to claim 1, wherein the primer layer contains tin oxide in an amount of 60% by weight or less based on the total amount of indium oxide and tin oxide.
3. The anti-reflection film according to claim 1 , wherein the thickness of the primer layer is from 0.5 nm to 20 nm.
4. The antireflection film according to claim 1 , further comprising an antifouling layer disposed on the antireflection layer opposite to the primer layer side.
5. The anti-reflection film according to claim 1 , wherein the hard coat layer contains particles having a number average primary particle diameter of less than 1.0 μm.
6. The anti-reflection film according to claim 1 , further comprising a pressure-sensitive adhesive layer disposed on the opposite side of the transparent film substrate to the hard coat layer.
7. An image display device comprising: an image display panel; and the anti-reflection film according to claim 1 disposed on a viewing side of the image display panel.
Citation Information
Patent Citations
Antistatic antireflection film
JP2004029126A
Manufacturing method of touch screen panel
KR1020140052510A
Antireflection film, method for producing same, and image display device
WO2021106788A1
Anti-reflection material and display device using the same
JP2005266665A